Retrospective Analysis of Checkpoint Inhibitor Therapy-Associated Cases of Bullous Pemphigoid From Six German Dermatology Centers - Sadik, Christian D.; Langan, Ewan A.; Gutzmer, Ralf; Fleischer, Maria Isabel; Loquai, Carmen; Reinhardt, Lydia; Meier, Friedegund; Göppner, Daniela; Herbst, Rudolf A.; Zillikens, Detlef; Terheyden, Patrick (Frontiers in Immunology, 2021)
Immune-related adverse events (irAEs) are a class-effect of checkpoint inhibitors (CIs). The development of a Bullous pemphigoid (BP)-like blistering disease, driven by autoantibodies against the hemidesmosomal protein BP180, is a potentially serious irAE whose incidence seems to be increasing. We therefore set out to characterize the clinical and (immuno)histopathological features and treatment responses of cases of BP which developed during or after CI therapy collated in six German tertiary referral centers between 2014 and 2018. We identified twelve cases of BP which emerged during and/or after CI therapy. The time interval between the initiation of CI therapy and the diagnosis of BP was 3–74 weeks (median: 23 weeks). Age at the time of diagnosis of BP varied between 62 and 80 years (median: 76 years). The clinical presentation of the patients was diverse but the severity was relatively mild when compared to that seen in most cases of spontaneous BP. Only four patients met all of the immunopathological criteria recommended in the European guidelines for the diagnosis of BP. Topical corticosteroid treatment was sufficient to achieve disease control in most patients. CI therapy could be continued in 8 out of 12 patients. In summary, our study indicates that cases of BP during or after CI therapy bear several peculiarities distinguishing them from spontaneous BP. Given the diversity of the clinical presentation of CI-induced BP the application of existing diagnostic algorithms developed for spontaneous BP can be utilized to uncover the frequency and features of CI-induced BP and to develop and optimize management algorithms.